PERAN ORANG TUA DALAM MENGAJARKAN KEBERSIHAN DIRI PADA ANAK USIA DINI - Masganti Sitorus; Lya Aurina Gayosa; Raudotul Ilmia; Salsabila Matondang (LPPM IAD Probolinggo, 2024)
Personal hygiene is one of the important aspects in the formation of character and health of early childhood. Parents have a major role in teaching personal hygiene to children through role models, motivation, and supervision. This study aims to analyze the role of parents in teaching personal hygiene to early childhood based on interviews with two parents. The results showed that parents exemplify personal hygiene to children through daily activities, such as washing hands before eating and brushing teeth before going to bed. Parent 1 focuses more on habits at home, while Parent 2 also teaches hygiene in the surrounding environment. In addition, the motivation given varies, from simple praise to creative awards, which are effective in encouraging children to practice personal hygiene. Supervision is also carried out consistently, both at home and outside the home. This study emphasizes the importance of collaboration between role models, motivation, and parental supervision in building children's personal hygiene habits from an early age. Keywords: personal hygiene; role of parents; early childhood